Efisiensi pakan benih ikan Gabus (Channa striata) menggunakan pakan komersial dengan persentase berbeda - Rustiana Widaryati (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This study aims to determine the efficiency of snakehead fish (Channa striata) seed feed using commercial feed with different percentages. Research using Completely Randomized Design (RAL) with 4 (four) treatment that is treatment A feeding pellet with 3% percentage, treatment B 5%, treatment C 7% and treatment D feeding trash fish with percentage 5% (Control). Parameters observed were feed efficiency, relative weight growth, survival rate and water quality. The result showed that commercial feeding had significant effect on the efficiency of feed utilization of snakehead fish seed. The highest feed efficiency was treatment C (7.0%) followed treatment D (6.8%), while the lowest was treatment A (6.1%). The relative weight growth of the highest was found in the treatment C (259.06), followed by D, C and the lowest was treatment A (241.76). Survival rate of fishes during the research was 100%. Water quality was in the range that still be tolerated by snakehead fish.